IMPROVEMENT OF rHDPE PLASTIC QUALITY USING SIX SIGMA AND TAGUCHI METHODS - Findiani, Rifka (JEMIS (Journal of Engineering & Management in Industrial System), 2019)
This study aims to determine the optimum process parameters in producing plastic bag in the application of Blown Film Extrusion Process. It is very critical to enhance product quality by optimizing the parameter, since preventing defected product not only can minimize cost but also can attract more customer. Recycled High Density PolyEthyelene (rHDPE) was studied in this experiment which widely used in both industry appliance and household. In accordance with the purpose of this research mentioned above, Six Sigma and Taguchi were adopted to define which factors and levels affected the quality of product, namely extruder temperature, extruder rotation, winder rotation,and take up rotation. The orthogonal array of Taguchi’s L 9 (3 4 ) was used to carry out the experimental plan. The effect of parameter was evaluated through weight measurement of specimen. The result of the study reveals that the quality of products were optimized under the process combination of extruder temperature 170ᵒC, 3,468 RPM screw rotation, rotation takes up 1,242 RPM, and winder rotation 1,620 RPM.